PREVENTION OF VIOLENCE, NEGLECT AND EXPLOITATION AGAINST CHILDREN REVIEWED FROM LAW NUMBER 35 OF 2014 CONCERNING CHILD PROTECTION - Anggriani, Jum; Indah Harlina; Yoyo Arifardhani; Utji Sri Wulan W; Finady, Andreas Sapta (PT Inovasi Pratama Internasional, 2025)
This community service program examines the implementation of Law Number 35 of 2014 concerning Child Protection in efforts to prevent violence, neglect, and exploitation of children in target communities. Using empirical legal methods with a legislative, participatory, and case approach, this program aims to socialize child protection policies, identify barriers to implementation at the community level, and formulate joint action strategies to optimize prevention efforts. The results of the community service show that although the legal framework for child protection has been strengthened, its understanding and implementation in the community still face structural, substantial, and cultural challenges. Inhibiting factors include low legal literacy in the community, lack of understanding of reporting mechanisms, limited access to protection services in the regions, and socio-cultural norms that still legitimize violence as a form of discipline. Optimization strategies developed together with the community include the establishment of village-level child protection forums, training of child protection cadres, community-based education campaigns, utilization of technology for reporting systems, and development of special protocols for handling cases in disaster situations. A collaborative approach involving community leaders, schools, families, and children themselves is key to the sustainability of child violence prevention programs in the community.